Modelling new products acceptance among retailers in Nigeria - Simon Adekunle; Jones Oghenemega Ejechi (Journal of Enterprise and Development (JED), 2022)
Purpose — The study modelled the determining factors affecting the acceptance of new products among retailers in Nigeria. Four antecedents of new product acceptance namely relationship quality, channel motivation, product advantage, and market competitiveness were explored.Research method — A cross-sectional survey research design was employed by using questionnaire to collect data for the study. The data obtained from eighty-six respondents were presented and analyzed using different statistical tools such as mean, correlation, and Partial Least Square Structural Equation Modelling (PLS-SEM) through the use of SmartPLS 3.0 software.Result — The study revealed that relationship quality and market competitiveness have positive and significant influence on new product acceptance among retailers. However, channel motivation and product advantage do not have a statistically significant influence on new product acceptance.Recommendation — The relationship between suppliers and retailers can be strengthened by taking advantage of the dynamic innovations in different social media platforms to establish uninterrupted links for effective communication. This study contributes to knowledge by adding to the emerging discourse on the strategic space occupied by retailers in guaranteeing the ultimate success of new products in the Nigerian business setting by providing insights on the determinants of new products acceptance among retailers.